Peripheral Bone Relapse of Paediatric TCF3-HLF Positive Acute Lymphoblastic Leukaemia during Haematopoietic Stem Cell Transplantation: A Case Report - Máté Horváth; Gabriella Kertész; Csaba Kassa; Vera Goda; Kata Csordás; Lidia Hau; Anna Kövér; Anita Stréhn; Orsolya Horváth; Krisztián Kállay; Gergely Kriván (MDPI AG, 2022)
The present case report features a highly uncommon form of a paediatric TCF3-HLF positive acute lymphoblastic leukaemia (ALL) relapse, an extramedullary, peripheral bone manifestation. Following complete remission, during the conditioning for haematopoietic stem cell transplantation (HSCT), our sixteen-year-old male patient complained of fever, pain and swelling of the right forearm. Radiography suggested acute osteomyelitis in the right ulna with subsequent surgical confirmation. Intraoperatively obtained debris culture grew Staphylococcus aureus and Acinetobacter pittii. Measures taken to control the infection were deemed to be successful. However, after the completion of the otherwise uneventful HSCT, a very early medullary relapse was diagnosed. Revising the original surgical samples from the ulna, bone relapse of ALL was immunohistochemically confirmed. Reviewing the previous cases found in the literature, it is advised to consider uncommon forms of ALL relapse when encountering ambiguous cases of osteomyelitis or arthritis during haematological remission.